Risk of Mortality on Patients with Traffic Accidents of Emergency Department at dr. Soebandi Hospital, Jember Regency - Baskoro Setioputro; Indah Listiyawati; Kholid Rosyidi Muhammad Nur (Universitas Airlangga, 2020)
Introduction: The number of deaths due to traffic accidents has become a global burden. In addition SDGs 2030 has set a target to decrease the number of fatalities and global injuries due to traffic accidents. The purpose of this study was to analyse the risk of mortality due to traffic accidents in the Emergency Department (ED) of dr.Soebandi Hospital Regional, Jember Regency.Methods: A retrospective observational study was carried out in the ED by studying medical records of the traffic accident patients aged ≥16 years. The sampling technique was simple random sampling with sample size 250. The study collected data with Modified Rapid Emergency Medicine Score. This study result was analyzed with frequency distribution and Chi-square test.Results: The result showed respondents who experienced traffic accidents were mostly 20-29 years old (19.6%). The majority of the patients were men (68.4%). The riders of two/three-wheeled vehicles who suffered traffic accidents reached 73.2%. Most of the accidents occurred between 06.00-11.59am, 37.6%. Generally, traffic accidents occur to drivers as much as 68.4% and the number of types of head trauma as much as 57.2%. This study showed that 94.8% patients were at low risk of mortality. There was significant relationship between risk of mortality and the role in vehicle use (p-value = 0.043).Conclusion: Almost all patients have a low risk of mortality in the ED of dr. Soebandi Hospital Jember Regency.